PERANCANGAN PERBAIKAN LAYANAN E- COMMERCE PT. X - Annisa Rahman, Puti
X is e-commerce that facilitates interaction between customers, property owners, property agents, developers, banks, and others. As a growing company, the company needs to survive and thrive in the industry. However, based on initial observation, there is currently a decrease in the net promoter score (NPS) of e- commerce X. In addition, there are still many complaints from customers. Therefore, it is important for companies to focus on improving service quality and customer satisfaction. Based on these problems, the root cause of the problem was the company hasn’t improved e-commerce based on the functional and emotional needs of customers. Therefore, it’s necessary to design service improvements based on customer needs with the integration of e-service quality, Kansei engineering, Kano model and TRIZ. The functional indicators that becomes the priority for improvement are “E-commerce X respond to customer needs quickly” and “E-commerce X provides appropriate solutions to customer complaints” which are significantly related to the emotional indicators of “Comfortable”, “Informative”, “Accurate”, “Flexible”, “Safe”, and “Communicative”. Proposed service improvements are to conduct intensive training programs for the customer service team, implement SOPs and SLAs in a disciplined manner in the process of responding to customer complaints, and develop existing and new features in the service.